The Needs Analysis of Attachment Technique for Teacher in Inclusive Primary School - Farhana, Surya; Asrowi, Asrowi; Subagya, Subagya (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This study aims to analyze the need for development a attachment technique to improve teacher pedagogical competence for students with special needs in inclusive primary schools. Analysis of the needs used is quantitative analysis. The research respondents were teachers primary inclusive schools in the city of Surakarta. This research is limited to the analysis of related approach  teachers to students with special needs conducted in inclusive schools. The results of this study indicate that 84% of teachers in inclusive schools still have difficulties to establish an approach. Teacher need to improve their competence one of them is guidance to support learning in their class.  The Attachment tecnique can be one is needed to teachers can apply to approach students with special needs conducted to support learning in their class.  Therefore, it is necessary to develop an attachment technique to improve teachers pedagogical competence.